Faculty and Staff Perspectives of a Behavior Assessment Team: A Case Study Evaluation - Greenstein, Kerry (2014)
Following the shooting at Virginia Polytechnic Institute in 2007, colleges began formally implementing threat assessment teams to help identify threats and prevent violence from occurring. On many campuses those teams have developed into Behavior Assessment Teams (BATs) that evaluate threats as well as support students by identifying concerning behavior and strategically implementing interventions to reduce the risk of violence. Many of those teams are now well established and need some method for evaluating their effectiveness. The purpose of this study was to understand faculty and staff perceptions of a campus BAT and evaluate a team’s effectiveness as defined by the team’s impact on campus culture, specifically as it relates to campus safety. Four specific aspects (the reporting process, the team’s response to a report, the observed changes in behavior following an intervention, and the impact on campus safety) were identified for review. Each of these areas came from literature regarding best practices for a BAT, and, collectively, were used to evaluate the team’s effectiveness. Using a case study approach the researcher interviewed 13 faculty and staff members from the campus that had previously submitted a report to the BAT. The researcher believed that community members who had previously worked with the team were in a better position to discuss their experiences and provide feedback about the team’s handling of cases than team members themselves. Additionally, this study included an analysis of team documents including the institution’s BAT policy and procedure manual, BAT website, reporting form, and selected case notes. The results indicated that the faculty and staff on this campus have a positive perception of the BAT and the work that it does. While there were acknowledgements of areas in which the team could improve, overall, the community felt like the team was effective. Responses indicated that people understood the reporting process, and that the team followed up quickly on reports that it received, providing students with resources as needed. Most importantly, the community members saw the BAT as playing an important role in regard to campus safety, whether for record-keeping purposes or to help intervene and prevent violence from occurring. Finally, the implications based upon these findings are included, along with recommendations for future research